2006
DOI: 10.1071/en05038
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate Removal from Aqueous Solutions using Neutralised Bauxite Refinery Residues (Bauxsol™)

Abstract: Environmental Context.Eutrophication of freshwater and marine ecosystems is a global problem, which is frequently linked to high phosphorus concentrations. The present study investigated the use of Bauxsol™, a modified bauxite refinery residue, to remove dissolved phosphate from water, and has shown that it can be used as a cost-effective adsorbent for treating phosphate-contaminated waters. The results provide water and environmental managers with a new technique for decreasing the phosphate loads in water an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(37 citation statements)
references
References 21 publications
3
33
1
Order By: Relevance
“…A c c e p t e d M a n u s c r i p t 13 kinetic parameters for pseudo first-order, Elovich and pseudo second-order models are given in Table 2. According to correlation coefficient R 2 , the pseudo second-order model fitted the adsorption process better than Elovich model and pseudo first-order model.…”
Section: Page 13 Of 44mentioning
confidence: 99%
See 1 more Smart Citation
“…A c c e p t e d M a n u s c r i p t 13 kinetic parameters for pseudo first-order, Elovich and pseudo second-order models are given in Table 2. According to correlation coefficient R 2 , the pseudo second-order model fitted the adsorption process better than Elovich model and pseudo first-order model.…”
Section: Page 13 Of 44mentioning
confidence: 99%
“…No study has systemically investigated how the phosphate reacted with AaN-RM. Akhurst et al [13] suggested that Page 6 of 44 A c c e p t e d M a n u s c r i p t 6 chemisorption could be important during phosphate adsorption by AaN-RM. The functional species on AaN-RM surface, which were responsible for the chemisorption, have not been identified.…”
Section: Introductionmentioning
confidence: 99%
“…The neutralisation of the soluble alkalinity for both Basecon™-neutralised and Hybrid materials requires the addition of Ca and Mg in a treatment solution, and the data suggests that the high Ca and Mg loadings of these two materials gives the corresponding increase in P binding. Higher P loadings data have been recorded when UNRM is neutralised using gypsum (Alkaloam™) than for UNRM (Akhurst et al, 2006;Brennan et al, 1994;Despland et al, 2011;Huang et al, 2008;Summers et al, 2000). Hence, a major mechanism for P removal to the solids would appear to be the precipitation of poorly soluble Ca-and Mg-phosphates, and such phosphates, although of low water solubility, remain plant available (Akhurst et al, 2006;Clark et al, 2008;Despland et al, 2011;Huang et al, 2008;Summers et al, 2000).…”
Section: Metal and Phosphate Loading Capacitymentioning
confidence: 93%
“…These applications are where retention of phosphorous is desired. Table 6 shows that removal rates of P to CNRM, compared to Basecon™-neutralised and Hybrid material, is substantially reduced, hence to control the same quantity of phosphorous requires nearly 4 times the dose rate (Akhurst et al, 2006;Clark et al, 2006;McConchie et al, 1999). Such applications for P removal are in sewage treatments, some soil remediation and in the control of farm effluents and fertiliser applications.…”
Section: Metal and Phosphate Loading Capacitymentioning
confidence: 96%
See 1 more Smart Citation